Measurement of Ckm Matrix Elements in Single Top Quark T-Channel Production in Proton-Proton Collisions at S=13 Tev - Sirunyan, A.M.; Tumasyan, A.; Adam, W.; Ambrogi, F.; Bergauer, T.; Dragicevic, M.; Sobol, A. (Elsevier B.V., 2020)
The first direct, model-independent measurement is presented of the modulus of the Cabibbo–Kobayashi–Maskawa (CKM) matrix elements |η|Vtb, |η|Vtd, and |η|Vts, in final states enriched in single top quark t-channel events. The analysis uses proton-proton collision data from the LHC, collected during 2016 by the CMS experiment, at a centre-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 35.9 fb−1. Processes directly sensitive to these matrix elements are considered at both the production and decay vertices of the top quark. In the standard model hypothesis of CKM unitarity, a lower limit of |η|Vtb>0.970 is measured at the 95% confidence level. Several theories beyond the standard model are considered, and by releasing all constraints among the involved parameters, the values |η|Vtb=0.988±0.024, and |η|Vtd 2+|η|Vts 2=0.06±0.06, where the uncertainties include both statistical and systematic components, are measured. © 2020 The Author
Keywords: Ckm Matrix; Cms; Physics; Top Quark